Exploring barriers refugees and refugee claimants experience accessing reproductive health care services in Toronto - Gateri, Hellen; Richards, Donna (My University, 2017)
Studies conducted in Canada and other countries with similar health care systems, such as Britain, Australia, and the Netherlands, demonstrate that refugees and refugee claimants experience barriers in accessing reproductive health care services, such as pre- and postnatal care and cervical cancer screening. These studies further indicate that the barriers that refugees and refugee claimants experience are largely due to racism and discrimination, culture, language, and/or communication. However, these studies rarely consider the broader political, economic, historical, and social contexts from which these women are attempting to access reproductive health care services. For example, they rarely consider the effects of neoliberal immigration policies and health care cut backs resulting from Canada’s adoption of a neoliberal ideology that supports minimal government intervention in the economy. Many of the studies reviewed emphasise cultural barriers, that is, the researchers assume that a woman’s culture is the most important determinant of their participation in reproductive health care services. When culture is viewed as the main problem attention is deflected from systemic racism and discrimination and other factors that impede access to reproductive health care services. These studies also fail to capture the unique gendered and racialised experiences of women refugees and refugee claimants and how these affect their access to reproductive health care services. To improve accessibility, most of these studies recommend culturally sensitive service delivery or increased awareness of racialised cultures among health professionals. Culturally sensitive or cross-cultural care, informed and shaped by neoliberal and multicultural policies, are popular approaches to addressing the needs of ethnic minority populations, or “multicultural others,” and managing ethnic or cultural diversity within the Canadian health care system. Guided by antiracist theories and postcolonial feminist theories, this paper argues that neoliberal ideology and multicultural discourse have effectively moved attention away from racism and other systemic barriers in Canadian society and attributed the problem of unequal access primarily to the cultures of women refugees and refugee claimants. In the multicultural paradigm, the structural and material differences or inequities among populations are reduced to the issue of ethnic and cultural diversity. The discourse of diversity overlooks power differences by explaining inequities in cultural terms that construct culture, along with ethnicity and community, as static and independent of social, historical, economic, and structural forces. As such new research is required to explore whether and to what extent women refugees and refugee claimants underutilise reproductive health care services, such as pre- and postnatal care and cervical cancer screening, taking into account not just culture but also the social, economic, political, and historical context from which the women are seeking health care services.
Keywords: women refugees; refugee claimants; reproductive health; race; gender; class and barriers